PENGARUH PENGANGGARAN PARTISIPATIF, SELF ESTEEM, LOCUS OF CONTROL, KAPASITAS INDIVIDU DAN KOMITMEN ORGANISASI TERHADAP BUDGETARY SLACK (Studi Pada OPD Kota Pekanbaru) - Humaira Basri; M Rasuli; Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the effect of participatory budgeting, self esteem, locus of control, individual capacity and organizational commitment to Budgetary Slack on OPD Pekanbaru City. The population in this study are structural officials, consisting of Echelon II, III, and IV. The sample in this study is structural officials who participated in regional budgeting amounting to 129 people. Methods of data collection using survey method in the form of questionnaires Sampling technique using purposive sampling. The model of hypothesis test data analysis in this research is multiple linier regression analysis model.The results of the study showed that: 1) participative budgeting had significant effect on budgetary slack, 2) Self esteem had significant effect on budgetary slack, 3) Locus of control had no significant effect on budgetary slack, 4) Individual capacity had significant effect on budgetary slack, and 5) organizational commitment has a significant effect on budgetary slack.Keywords: participatory budgeting, self esteem, locus of control, individual capacity, organizational commitment, budgetary slack,